2014
DOI: 10.1002/jmor.20312
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in the microanatomy of cosmetid harvestmen (Arachnida, Opiliones, Laniatores)

Abstract: Scanning electron microscopy (SEM) is a useful tool for identifying interspecific variation in often overlooked structures that may represent useful sources for informative phylogenetic characters. In this study, we used SEM to compare the morphology of 12 cosmetid species from Central America, the Caribbean, and North America including multiple species for the genera Cynorta, Erginulus, and Paecilaema. To determine if microanatomical structures were unique to the cosmetid taxa under examination, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…They exhibited interspecific variation with respect to occurring on the surface of the cuticle and in the prominence of the pores (Table 2). Rodriguez et al (2014) found rough pit glands to be common on the ocularium and anterior region of the dorsal scutum in these same species of cosmetid harvestmen, but absent from other gonyleptoidean harvestmen, with the notable exceptions of agoristenid and gonyleptid species. In our study, rough pit glands were generally absent from the legs of agoristenid harvestmen, but present on the legs of most gonyleptids (Glysterus sp.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…They exhibited interspecific variation with respect to occurring on the surface of the cuticle and in the prominence of the pores (Table 2). Rodriguez et al (2014) found rough pit glands to be common on the ocularium and anterior region of the dorsal scutum in these same species of cosmetid harvestmen, but absent from other gonyleptoidean harvestmen, with the notable exceptions of agoristenid and gonyleptid species. In our study, rough pit glands were generally absent from the legs of agoristenid harvestmen, but present on the legs of most gonyleptids (Glysterus sp.…”
Section: Discussionmentioning
confidence: 92%
“…An ultrastructural study of porous and nonporous rough pit glands is needed to resolve this issue. On the basis of their relatively high abundance on multiple leg segments (present study) and the dorsal scutum (especially the ocularium: Rodriguez et al 2014), we hypothesize that rough pit glands may represent phylogenetically informative structures at the familial level. Within the Cosmetidae, the usefulness of rough pit glands (morphology or distribution) as characters for identifying genera or species is less clear.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations